2011
DOI: 10.1080/21580103.2011.621377
|View full text |Cite
|
Sign up to set email alerts
|

Tree biomass and carbon stock of a community‐managed mangrove forest in Bohol, Philippines

Abstract: Mangrove plays a significant role in climate change mitigation particularly in carbon absorption and minimizing the detrimental impacts of sea level rise, saltwater intrusion and tidal surges. In Bohol Province, Philippines, a small coastal island community known as Banacon is one of the successful cases in mangrove reforestation. Recognizing the site's potential for a carbon sequestration project, a biomass and carbon stock assessment of mangrove trees was done. Using standard sampling techniques and allometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 16 publications
6
38
1
4
Order By: Relevance
“…The overall mean BGB biomass is 53.8  4.5 t/ha (C-stock of 26.9  2.2 t-C/ha), while plantation stands is 55.7  9.8 t/ha (C-stock of 27.98  4.9 t/ha) and natural stands is 53.3  5.2 t/ha (C-stock of 26.6  2.6 t-C/ha). The values of mean BGB and carbon stock (53.8  4.5 t-C/ha and 26.9  2.2 t-C/ha respectively) in MMW show comparatively higher C-stock than mangrove forests in Northern Vietnam 42 , southern China 43 and Tamil Nadu (India) 13 . But, in the present study C-stock value is much lower than that in mangrove forests in Bahile (Philippines) 44 , Bohol (Philippines) 13 and Yap 45 .…”
Section: Field Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall mean BGB biomass is 53.8  4.5 t/ha (C-stock of 26.9  2.2 t-C/ha), while plantation stands is 55.7  9.8 t/ha (C-stock of 27.98  4.9 t/ha) and natural stands is 53.3  5.2 t/ha (C-stock of 26.6  2.6 t-C/ha). The values of mean BGB and carbon stock (53.8  4.5 t-C/ha and 26.9  2.2 t-C/ha respectively) in MMW show comparatively higher C-stock than mangrove forests in Northern Vietnam 42 , southern China 43 and Tamil Nadu (India) 13 . But, in the present study C-stock value is much lower than that in mangrove forests in Bahile (Philippines) 44 , Bohol (Philippines) 13 and Yap 45 .…”
Section: Field Samplingmentioning
confidence: 99%
“…The values of mean BGB and carbon stock (53.8  4.5 t-C/ha and 26.9  2.2 t-C/ha respectively) in MMW show comparatively higher C-stock than mangrove forests in Northern Vietnam 42 , southern China 43 and Tamil Nadu (India) 13 . But, in the present study C-stock value is much lower than that in mangrove forests in Bahile (Philippines) 44 , Bohol (Philippines) 13 and Yap 45 . The above-ground and below-ground biomass ratio (T/R ratio) for the present study ranged from 2.0 to 2.6, or an average of 2.3.…”
Section: Field Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Mangrove ecosystems also support high floral and faunal biodiversity [9,[12][13][14] and sequester significant amounts of CO 2 [15,16]. While numerous studies have measured above-ground biomass in mangrove trees (e.g., [17][18][19][20][21][22][23][24][25][26]), comparatively few have quantified above-and below-ground carbon (C) pools, including soil (i.e., [15,[27][28][29][30][31][32][33][34]); however, it is the deep, organic material enriched soils that contain the vast majority of C stocks [35][36][37][38]. Factoring in soil, mangroves have been found to be amongst the most carbon-dense forests in the tropics, with similar or greater above-and exceptionally larger below-ground stocks compared with the terrestrial systems reported in several studies [15,27,[32][33][34]39].…”
Section: Introductionmentioning
confidence: 99%